Studi Tingkah Laku Makan dan Berkubang Kerbau Lumpur (Bubalus bubalis carabanesis) di Desa Teluk Kayu Putih - Nining Nuraida; Try Susanti (Universitas PGRI Silampari, 2024)
This study is to investigate the feeding and washing habits of swamp buffaloes (Bubalus bubalis carabanesis) in Teluk Kayu Putih Village, VII Koto District, Tebo Regency. This study was carried out from July to October 2023, involving a sample of 5 buffalo. The sample included adult male and female buffalo, as well as immature male and female buffalo (referred to as